Efektifitas Model Pembelajaran Learning Cycle 5E Pada Pembelajaran Fisika Siswa Kelas VII SMP Negeri 6 Lubuklinggau - Selvi Karlina; Endang Lovisia (Journal on Education, 2024)
This research is entitled "The effectiveness of the 5e learning cycle learning model in physics learning for class VII students at SMP Negeri 6 Lubuklinggau. 2024/2025 academic year." The aim of this research is to determine the completeness of the physics learning outcomes of class VII students at SMP Negeri 6 Lubuklinggau for the 2024/2025 academic year after implementing the Learning cycle 5e learning model. The method used is quasi-experimental with a one group pretest-posttest research design. The population in this study were all class VII students of SMP Negeri 6 Lubuklinggau for the 2024/2025 academic year, totaling 157 students and the research sample was class VII 7 3 students, totaling 26 students, consisting of 13 male students and 13 female students who were taken. at random. Data collection techniques use test techniques. Student test score data was analyzed using the t test. Abstrak Penelitian ini berjudul “efektifitas model pembelajaran learning cycle 5e pada pembelajaran fisika siswa kelas VII SMP Negeri 6 Lubuklinggau. Tahun Pelajaran 2024/2025”.Tujuan penelitian ini adalah untuk mengetahui ketuntasan hasil belajar fisika siswa kelas VII SMP Negeri 6 Lubuklinggau tahun pelajaran 2024/2025 setelah diterapkan model pembelajaran Learning cycle 5e. Metode yang digunakan adalah Quasi eksperimen dengan desain penelitian one group pretest-posttest design. Populasi dalam penelitian ini adalah seluruh siswa kelas VII SMP Negeri 6 Lubuklinggau tahun pelajaran 2024/2025 yang berjumlah 157 siswa dan sampel penelitian adalah siswa kelas VII 7 3 yang berjumlah 26 siswa, yang terdiri dari 13 siswa laki-laki dan 13 siswa perempuan yang diambil secara acak. Teknik pengumpulan data menggunakan teknik tes. Data skor tes siswa dianalisis dengan menggunakan uji t.